How has the Covid-19 pandemic effected innovation in the healthcare system in Iceland? - Atli Sæmundsson 1991- (2020)
This study aims to demonstrate the positive relationship between the Covid-19 pandemic and innovation in the Icelandic healthcare system, using a conceptual model of public sector corporate entrepreneurship. The study aims to explore and examine predecessor for innovation in the public sector and give a detailed information on how the effects of the Covid-19 pandemic has had on innovation in the healthcare system and answering the question: How has the Covid-19 pandemic effected innovation in the healthcare system in Iceland? Qualitative method, where semi-structured interviews were conducted with five large stakeholders of the healthcare system in Iceland, was used with the objective to determine the effect from the Covid-19 pandemic on innovation. The study provides an in-depth breakdown of corporate entrepreneurship dimensions, based on public sector organizations and external environment factors, that are predecessor for innovation. Findings from the research indicate that the healthcare system in Iceland has a positive attitude towards innovation, but lack of resources and communication can prove as being a prohibiting factor for innovation to occur. Therefore, by exploiting the opportunity to analyze how the catalyzing effects on how the Covid-19 pandemic effected innovation, the healthcare system can gain further information on how to embrace innovation. All participants in the study, acknowledged the positive relationship between Covid-19 pandemic and innovation, and provided vital information on how innovative solutions can be beneficial for the healthcare system. Empirical findings suggest that the effects from the Covid-19 pandemic on innovation, consist mainly of: Increased flexibility, better use and sharing of resources, more motivation and encouragement as well as increased communication. Additionally, the research gives a foundation for the relevancy to investment and manage innovation in the healthcare system and provides a platform for future research in healthcare innovation in Iceland.